The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.7554/elife.21199
|View full text |Cite
|
Sign up to set email alerts
|

RAGE deficiency predisposes mice to virus-induced paucigranulocytic asthma

Abstract: Asthma is a chronic inflammatory disease. Although many patients with asthma develop type-2 dominated eosinophilic inflammation, a number of individuals develop paucigranulocytic asthma, which occurs in the absence of eosinophilia or neutrophilia. The aetiology of paucigranulocytic asthma is unknown. However, both respiratory syncytial virus (RSV) infection and mutations in the receptor for advanced glycation endproducts (RAGE) are risk factors for asthma development. Here, we show that RAGE deficiency impairs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 53 publications
(69 reference statements)
1
31
0
Order By: Relevance
“… 70 We are currently testing this possibility using mouse models of experimental asthma. Various models have been described, 120 including those that mimic mechanisms underlying acute allergic asthma; 121 , 122 chronic asthma; 123 and viral-induced asthma 124 in humans. It is not always straightforward to decide which model is most appropriate to use, and different models can result in different findings, 100 presumably because of the different underlying pathophysiology.…”
Section: Opportunities and Challengesmentioning
confidence: 99%
“… 70 We are currently testing this possibility using mouse models of experimental asthma. Various models have been described, 120 including those that mimic mechanisms underlying acute allergic asthma; 121 , 122 chronic asthma; 123 and viral-induced asthma 124 in humans. It is not always straightforward to decide which model is most appropriate to use, and different models can result in different findings, 100 presumably because of the different underlying pathophysiology.…”
Section: Opportunities and Challengesmentioning
confidence: 99%
“…Consistent with this theory, IL-2/IL-33-stimulated ILC2s produced IL-13 in a biphasic manner, with the second phase occurring after the peak of HMGB1 release (Fig 6B). As we had previously shown that RAGE -/mice generate attenuated type-2 inflammatory responses to both viral-or allergen-triggered experimental asthma [6,37], we speculated that HMGB1/RAGE ligation promotes type-2 cytokine production by ILC2s. To determine whether ILC2s express RAGE, we used RAGE -/mice in which the functional Ager gene has been replaced by GFP.…”
Section: Ilc2-derived Hmgb1 In Irf7 -/Mice Acts In An Autocrine Mannementioning
confidence: 89%
“…Asthma is a polygenic disorder, underpinned by gene-environment interactions. As individual SNP effects on disease risk are small, we elected to use knockout mice, which we have used previously to identify novel pathogenic mechanisms [34,37,47]. We believe this approach is preferable to using an extremely high inoculum in WT mice that can induce non-physiological responses and increase the potential for false positives.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…Moving toward the plasma membrane, HMGB1 binds RAGE, a receptor also expressed in epithelial cell cultures ( 28 ) and able to exacerbate RSV disease by amplifying the expression of proinflammatory agents. RAGE deficiency has been associated with viral-induced asthma phenotype in a mouse model ( 29 ). Our data also confirmed nuclear HMGB1 localization during the early phase of infection, which has been shown to be a critical initial event for an efficient viral cycle ( 4 ).…”
Section: Discussionmentioning
confidence: 99%